Bridging Tradition and Innovation: Incorporating Indigenous Engineering Practices into Ghana’s Secondary School Curriculum - Francis, Kwateng; Wai Yie, Leong (INTI International University, 2025)
Despite the richness of Ghanaian Indigenous Knowledge Systems (IKS), their absence in secondary school engineering education renders them irrelevant and uninspiring. This study explores incorporating IKS into Ghanaian second-cycle engineering curricula to advance cultural identity and contextual relevance. Using a mixed-method approach, data were collected from students, instructors, curriculum developers, and local artisans through questionnaires, interviews, and focus group discussions. Findings confirm broad support for integrating indigenous technologies like mud construction and kente weaving. Teachers and students emphasized scientific and mathematical foundations, while curriculum planners focused on compatibility with Ghana’s Common Core Programme. IKS is positioned as “local STEM,” enhancing student enthusiasm, cultural pride, and environmental responsibility. Issues of teacher preparation and resource limitations emerged, prompting calls for systemic reform. The study outlines a culturally responsive model of engineering education that bridges formal schooling and indigenous practice, calling for curriculum redesign, policy changes, and strong community collaboration.